PERBEDAAN UMUR, PENDIDIKAN, PELATIHAN DAN PENGETAHUAN PADA WIRAUSAHA PRAKTIK KEBIDANAN KOMPLEMENTER DI KECAMATAN CIRACAS - Herselowati, Herselowati; Pawestri, Nui (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Economic growth is an increase in the value and amount of production of goods and services calculated by a country within a certain period of time. Midwifery graduates can practice conventionally or complementaryly. Entrepreneurship is an important element in economic development. The aim of the research is to determine differences in age, education, training and knowledge in complementary midwifery practice entrepreneurs in Ciracas sub-district. This research is a quantitative analytical research using a cross sectional approach. The total population in this study was 64 midwives. The researcher took samples using a total sampling technique in Ciracas sub-district in 2023. This research was conducted during September – October 2023. Research analysis used chi squer. The results of this research show that there is a significant difference between age (pValue: 0.403), education (pValue: 0.037), training (pValue: 0.018) and there is no significant difference between knowledge (pValue: 0.098) and complementary practice entrepreneurship in midwife in the Ciracas sub-district area. The conclusion of this research is that there are significant differences between age, education and training and entrepreneurship in the complementary practices of midwives. It is recommended in this research that midwives continue to increase their knowledge about complementary midwifery to be motivated to practice complementary midwifery services.